Littoral zooplankton diversity in Himayat Sagar Reservoir, Telangana, India. Issue 1 (7th January 2021) - Karuthapandi, Madasamy; Jaiswal, Deepa
Abstract: The present study investigated zooplankton composition and diversity, along with physicochemical parameters from the littoral regions of Himayat Sagar Reservoir, Telangana, India. A total of 84 zooplankton species were found, including 60 rotifer species, 16 cladoceran species and eight copepod species. Keratella tropica, Lecane bulla, Coronatella rectangula and Mesocyclops sp. were observed frequently throught the study period. The Shannon Diversity Index ranged between H ′ = 1.8 and 2.1, with a high diversity observed during the summer season. Dominance was greater during the monsoon and winter seasons, being represented by Brachionus calyciflorus, B. angularis, B. falcatus, Keratella tropica, Ceriodaphnia cornuta, Diaphanosoma sarsi and Mesocyclops sp. Correlation coefficients and principal component analysis indicated temperature, pH and nutrients had a major influence on zooplankton community changes in this reservoir. The environmental variables and diversity indices indicated seasonally fluctuating trophic conditions. Himayat Sagar Reservoir requires long‐term monitoring for assessment and better management of its faunal diversity and water quality.